Practical Substitution for the Indole, Methyl Red, Voges-Proskauer, Citrate System - Von Graevenitz, Alexander (1971)
A substitution for the indole, methyl red, Voges-Proskauer, citrate system is proposed. The scheme employs indole and ampicillin susceptibility tests routinely and uses selectively three other media for six reactions.